Sperm l1o~. o a dioleus pleurocarpous moss colonies, Anomodon virica¡osus (1-lech.) llook. & l’a~l., by a transplant experimení - Granzow de la Cerda, Íñigo (Botanica Complutensis, 1989)
. GRAN/OW DE LA CERDA. 1. 1989. Sperm 1kw a dioicus pleurocarpous rnoss colonies. Anomodon viticulosus (I-ledw.) Hook. & Tayl., by a transplant experiment. flor. Complot cnsis 15: 91--100 ( in Spa ni sh). 92 Granzow de la Cerda, 1 Transplant experiments were carried out between male and female colonies of Ihe pleurocarpous moss Anomodon viticulosus (Hedw.) Hook. & Tayl. in the eastern Pre-Pyrenees (Gerona, Spain). The purpose was to estimate the distance tbat sperm can be carried downwards by water down-flow or seepage. 20-30 >< 10-15 centimeter blocks of colonies witli antheridia were placed aboye unisexual female colonies. After a year, these had produced sporophytes for the fírst time. Ilie distance between the new sporophytes and the blocks with male plants, aboye, was found lo be at least 25 cm.
Keywords: Anomodon vitículosus; dioicous; fertilization pleurocarpous; sperm sperm flow; sporohytes; stem flow transplants